UJI SITOTOKSISITAS EKSTRAK ETANOLIK DAUN SAMBILOTO (Andrographis paniculata (Burm. f.) Nees) TERHADAP SEL RAJI (Kajian secara in Vitro) - Nisa Nafi'ah Oktaviani (FKG 16 UMY 066, 2016)
Background : Cancer is one of the main death causes in the world. Raji cells comes from Burkitt’s Lymphoma cancer especially B lymphocyte. Conventional cancer therapies such as chemotherapy, radiation, surgery and combination has many negative side effects for the patient’s body, therefore, cancer therapies with minimum side effects using herbs are still needed. The extract of Andrographis paniculata (Burm. f.) Nees leaves has an andrographolide active compound that work as an anticancer. Objective : The objective of this study is to test the cytotoxicity potency of ethanolic extract of Andrographis paniculata (Burm. f.) Nees towards raji cells. Methods : Cytotoxic test was using MTT assay (Microculture Tetrazolium Salt), absorbances reading using ELISA (Enzyme Linked Immunosorbent Assay) microplate reader with 550 nm wavelength. The type of this study is a pure laboratory in vitro experiment. Raji cells were given the ethanolic extract of Andrographis paniculata (Burm. f.) Nees leaves in a different concentrations which are (0; 3,125; 6,25; 12,5; 25; 50)μg/ml. Results : The result of this study is that the highest potency of ethanolic extract of Andrographis paniculata (Burm. f.) Nees leaves on destroying raji cells in 50μg/ml concentration with cell destroyed was 68,9%. Regression test using SPSS (Statictical Product and Service) shows that ethanolic extract of Andrographis paniculata (Burm. f.) Nees leaves towards raji cells has an IC50 in the amount of 11,60 μg/ml.